2020
DOI: 10.3390/ani10081287
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Group Lethal Gang Aggression in Domestic Pigs (Sus scrofa domesticus)

Abstract: Intraspecific coalitional aggression is rare among all species, especially within stable social groups. We report here numerous cases of intraspecific lethal gang aggression within stable groups of domestic pigs. The objective was to describe this extreme aggression and to identify potential causes. Management data were collected from farms with (n = 23) and without (n = 19) gang aggression. From one farm, 91 victims were assessed for skin injuries and body condition score. Lethal gang aggression was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…It has been found that gang aggression is neither related to the genetic lineage of the pigs nor dependent on the type of feed and occurs independently of sex. This type of behaviour has never been studied before because it was thought to be very rare (Camerlink et al, 2020). Nevertheless, it has been shown that, despite their seemingly marginal nature, these behaviours have a significant impact on animal performance on farms where they occur since they lead to mortality in growing pigs (Camerlink et al, 2020).…”
Section: Individuality Of Farm Animals Variation Of Behavioural Trait...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that gang aggression is neither related to the genetic lineage of the pigs nor dependent on the type of feed and occurs independently of sex. This type of behaviour has never been studied before because it was thought to be very rare (Camerlink et al, 2020). Nevertheless, it has been shown that, despite their seemingly marginal nature, these behaviours have a significant impact on animal performance on farms where they occur since they lead to mortality in growing pigs (Camerlink et al, 2020).…”
Section: Individuality Of Farm Animals Variation Of Behavioural Trait...mentioning
confidence: 99%
“…This type of behaviour has never been studied before because it was thought to be very rare (Camerlink et al, 2020). Nevertheless, it has been shown that, despite their seemingly marginal nature, these behaviours have a significant impact on animal performance on farms where they occur since they lead to mortality in growing pigs (Camerlink et al, 2020). The above observations may be evidence of the role of individualised yet infrequent personality traits predisposing some animals to leadership in so-called pig gangs that attack individuals lower in the hierarchy.…”
Section: Individuality Of Farm Animals Variation Of Behavioural Trait...mentioning
confidence: 99%
“…In commercial pig production, reducing the expression of harmful social behavioural traits, such as ear manipulation and tail biting and increasing the positive response to human handling, are of major interest. Ear manipulation and tail biting represent the main forms of harmful social behaviour in pigs [ 1 ], as they cause injuries, suppress immunocompetence, decrease growth rate and feed efficiency, and increase the risk of mortality [ 2 ]. As such, they significantly compromise animal welfare and economic and environmental sustainability.…”
Section: Introductionmentioning
confidence: 99%